PERANCANGAN SISTEM MANAJAMEN INSIDEN KEAMANAN INFORMASI BERDASARKAN SNI ISO/IEC 27035 DI INSTANSI PEMERINTAH - -, Wikankara; Hartanto, Rudy; Nugroho, Lukito Edi (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2020)
The government services of information technology are required to always run optimally. On the other hand, many information services are still faced with security incidents. In terms of human resources, technology, policy, and procedural aspects, the focus problem has not been on security incidents of information. Therefore, we need information security incident management system as one of the system solutions that must be provided to ensure the sustainability of information services and IT systems. The purpose of this research is able to provide security information of incidents having a management system that was adopted and developed based on ISO/IEC 27035 standardization. The research methodology was carried out by using qualitative methods with case studies. The preparation of the document refers to the results of the assessment approach between the current conditions of business processes and the incident management of information security. It has been carried out with the clauses required by ISO/ IEC 27035. The results of this study are policy documents and procedures for the incident management systems of information security specifically designed as a reference standard in government. Finally, the use of structured policies and procedures can improve performance in handling incidents faced by the government.